Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
a)(-13+8)*(-2)
(-5)*(-2)=10
b) (3-7)*(15-6)
-4*9=-36
c)(17-5):(-3)
12:(-3)=(-4)
d) (-5)*2*(-7)
(-10)*(-7)= 70
e)(-3)*(-2)*(-4)
6*(-4)=-24
f)((-6)*(-5)):(-15)
30:(-15)=(-2)
g)(-5)*(-2)+6*(-3)
10+6*(-3)
10+(-18)=(-8)
h)-25:(-2+7)-3
-25:5-3
-5-3=-8
i)((-8+2):3)*(8-15)
(-6:3)*7
-2*7=-14
j)(-4-5+2)2
(-9+2)2
(-7)2 = 49
k)(3-7+2)3
(-4+2)3
(-2)3=-8
l)(-5+2)2-(-2)*(-5)2
(-3)2+2*25
9+2*25
9+50=59
[tex]zad13[/tex]
[tex]a)(-13+8)*(-2)=(-5)*(-2)=10[/tex]
[tex]b)(3-7)*(15-6)=(-4)*9=(-36)[/tex]
[tex]c)(17-5):(-3)=12:(-3)=(-4)[/tex]
[tex]d)(-5)*2*(-7)=(-10)*(-7)=70[/tex]
[tex]e)(-3)*(-2)*(-4)=6*(-4)=(-24)[/tex]
[tex]f)((-6)*(-5)):(-15)=30:(-15)=(-2)[/tex]
[tex]g)(-5)*(-2)+6*(-3)=10-18=(-8)[/tex]
[tex]h)-25:(-2+7)-3=-25:5-3=-5-3=-8[/tex]
[tex]i)((-8+2):3)*(8-15)=(-6:3)*(-7)=(-2)*(-7)=14[/tex]
[tex]j)(-4-5+2)^{2}=(-9+2)^{2}=(-7)^{2}=49[/tex]
[tex]k)(3-7+2)^{3}=(-2)^{3}=-8[/tex]
[tex]l)(-5+2)^{2}-(-2)*(-5)^{2}=(-3)^{2}+2*25=9+50=59[/tex]